Entre a memória e a história : a historiografia da independência nos cem anos da emancipação - Käfer, Eduardo Luis Flach (2016)
This dissertation aims at analyzing the relation between memory and historiography, having as object of study some productions released during the commemorations of the 100th anniversary of Brazil’s Independence. A first instance, dedicated to memory, points to some images of the emancipation that were builtt after its success, as well as to the meaning that these images intended to carry. After that, based on the theory of Jörn Rüsen, who understands historical narrative as an intellectual operation capable of ensuring men’s identity before time, some historiographical productions from this period will be analyzed. The conferences of the Brazilian Historic and Geographic Instititute, in celebration of the 100 years of Independence, Francisco Adolfo Varnhagen’s A History of Independence, posthumously published, and Manuel de Oliveira Lima’s The movement of Independence, are highlighted. The objective then is to perceive how this apparent tension between memory, understood as an image of the past susceptible to imagination, and, historiography, seen as an intellectual operation in which research results and rationalizations about this same past are developed in written form, happens.